0937 Worst Nightmares Versus Idiopathic Nightmares: A Content Analysis. (27th April 2018) - Zadra, A; Robert, G; Duquette, A; English, V
Abstract: Introduction: Numerous studies have investigated different aspects of nightmares (e.g., frequency, association to psychopathology), but relatively few have examined nightmares' thematic content. We investigated the content of the worst nightmare recalled by men and women and compared the results to those previously obtained with idiopathic nightmares. Methods: Written reports of the worst nightmare ever experienced were obtained from 78 men (mean age = 25.5 ± 10.2 years) and 78 women matched for age (mean age = 25.2 ± 9.7 years) via a questionnaire assessing a variety of sleep and dream experiences. Variables of interest included the nightmares' thematic content and narrative development. Results: Men and women reported that their worst nightmare occurred at 14.2 and 15.1 years of age, respectively. The mean length (word count) of men's worst nightmare was 73.8 ± 40.9 words and 81.2 ± 36.8 words for women. 53% of men and 63% of women reported that their worst nightmare reoccurred over time. The two most frequently reported themes by men as well as women were being confronted by evil forces (21%) and being chased (12%). Other commonly reported themes included being physically attacked (M=8%, W=17%), environmental anomalies (M=4%, W=8%), helplessness (M=6%, W=8%) and health-related problems (M=5%, W=4%). As was true for idiopathic nightmares, men's worst nightmares were more likely to contain themes of large-scale disasters (e.g., wars, tornados, end of the world) than were women's nightmares. While the theme of evil forces was twice as frequent in worst nightmares than in idiopathic nightmares, themes involving interpersonal conflicts were rare (2.5%) even though they characterize 20% of idiopathic nightmares. Worst and idiopathic nightmares showed similarities in terms of narrative development (how dreams turn into nightmares), including their ending. Contrary to popular belief, themes of falling were rare, occurring in less than 3% of all nightmares. Conclusion: These findings reveal that unlike idiopathic nightmares, worst nightmares contain a restricted range of themes centred around malevolent forces, pursuit and physical aggression and that their content profiles show few gender differences. Support (If Any): Research supported by a grant from the Social Sciences and Humanities Research Council of Canada